La fabrique du musée universel ou les récits en question. Accessibilité, hiérarchie et transmissions - Marion Bertin; Marie-Alix Molinié-Andlauer (Miranda: Revue Pluridisciplinaire du Monde Anglophone, 2025)
At the beginning of the 21st century, the idea of the “universal museum” gained ground, with a narrative that sought to legitimize the preservation of certain objects in Western Museum collections. The narratives supporting this label include the accessibility of these collections, the lack of hierarchy within the walls of “universal museums,” and the challenge of transmission. Initially associated with major institutions in Europe and North America, the term ‘universal museum’ now refers to other, newer institutions in Africa and the Arab Persian Gulf that are either opening up to or reappropriating new forms of narrative. Yet universality in the museum is also reflected in temporary exhibitions of various kinds, reflecting tensions in the world and providing a home for artists in exile. Here we analyze three features of the universal in the museum and highlight the new narratives that emerge in response to our main hypothesis, namely that the emergence of universal museums in other parts of the world is being reconfigured as global circulations are redefined.